A novel zero-liquid discharge desalination system based on the humidification-dehumidification process: A preliminary study. (1st December 2021) - Chen, Qian; Akhtar, Faheem Hassan; Burhan, Muhammad; M, Kumja; Ng, Kim Choon
Highlights: A novel zero liquid discharge system based on humidification-dehumidification process is proposed; Salt separation from concentrated desalination brine is experimentally demonstrated; Energy consumption is reduced by 56% compared to existing processes; Initial cost is 58% lower than evaporative crystallizers; Abstract: As a byproduct of desalination plants, brine is increasingly becoming a threat to the environment, and the design of zero-liquid discharge (ZLD) systems is gaining increasing attention. Existing ZLD systems are limited by a high energy intensity and high plant costs of their crystallizers. This study proposes a novel crystallization method based on the humidification-dehumidification (HDH) process, which exhibits the advantages of a low energy consumption, low component costs and a reduced scaling and fouling potential. A simple experimental setup is first designed to demonstrate the feasibility of the proposed system. Brine concentration and salt crystallization are successfully achieved with air heated to 40 °C as the heat source. Afterwards, a thermo-economic analysis is conducted for the whole system. The specific thermal energy and electricity consumption levels are found to range from 700-900 and 5-11 kJ, respectively, per kg of feed brine. The energy consumption is 56% lower than that of a conventional evaporative crystallizer, and the initial plant cost is reduced by 58%. Graphical abstract: Image, graphical abstract